Heat-induced explosive spalling of self-prestressing, self-compacting concrete slabs. (3rd April 2023) - Mohammed, Hussein; Sultangaliyeva, Fariza; Wyrzykowski, Mateusz; Terrasi, Giovanni Pietro; Bisby, Luke
Highlights: Production of stable self-prestressed concrete samples. Previously unreported heat induced explosive spalling experiments using a novel concrete mix. Mitigation of heat induced spalling using PP fibres. Abstract: A novel concrete mix has been developed that can achieve high levels of self-prestressing through the controlled expansion of the concrete sample with cast-in carbon fibre reinforced polymer (CFRP) bars. Experiments have shown that the mechanical properties and durability of the mix are not adversely affected by the mix's self-expanding nature. However, the behaviour of this mix at elevated temperatures is largely unknown, raising legitimate concerns regarding the fire performance of the resulting self-prestressed concrete elements. The research presented in this paper investigates the behaviour of concrete elements manufactured from self-prestressed, self-compacting concrete (SPSCC) when exposed to severe heating – such as would likely be experienced during a building fire. Nine specimens, with dimensions (600 mm × 200 mm × 45 mm) were tested under one-sided exposure to an experimentally simulated ISO 834 standard heating regime. The results showed that the SPSCC samples were acutely prone to explosive spalling under these conditions. The results also suggest that the comparatively higher moisture content of SPSCC samples, as compared with conventional concrete mixes of similar composition and mechanical properties, appeared to be the most critical factor for heat-induced concrete cover spalling. Higher prestress (compressive) forces also appeared to exacerbate the spalling likelihood of SPSCC samples. The addition of 2 kg/m 3 of polypropylene (PP) fibres led to the complete elimination of spalling in SPSCC samples. The self-prestress levels in samples with PP fibres were 30 % less than those without PP fibres, for reasons which require additional investigation. Differential thermal expansion between the internal CFRP bars and the concrete was observed to restrain the elongation and thermal curvature of the samples during heating, up until the point where the bars debonded from the surrounding concrete due to elevated temperature and (presumed) increased tensile stress in the tendon anchorage zones. The results provide compelling evidence supporting the need to include PP fibres within high-performance, self-prestressing, self-compacting concrete slabs.